Successful surgical management of congenital Kasabach–Merritt syndrome. Issue 1 (January 2017) - Pascal, Sébastien; Bettex, Quentin; Andre, Nicolas; Petit, Philippe; Casanova, Dominique; Degardin, Nathalie
Abstract: Since the first description of Kasabach–Merritt syndrome (KMS) in 1940, many treatments have been proposed combining pharmacologic and non‐pharmacologic approaches, which can be effective on the pathology but can have adverse and unpredictable side‐effects with long‐term use. Herein we describe the solely surgical treatment of Kasabach–Merritt syndrome in a neonate with a severe and rapidly progressive thrombocytopenia. The patient's condition normalized at 7 days postoperatively, with rapid increase in platelet count and normalization ofd ‐dimer concentration.